A novel model for treatment of hypertrophic pachymeningitis. Issue 3 (15th January 2019) - Cui, Yiwen; Masaki, Katsuhisa; Zhang, Xu; Yamasaki, Ryo; Fujii, Takayuki; Ogata, Hidenori; Hayashida, Shotaro; Yamaguchi, Hiroo; Hyodo, Fuminori; Eto, Hinako; Koyama, Sachiko; Iinuma, Kyoko; et al.
Abstract: Objective: Immunoglobulin (Ig)G4‐related disease is a major cause of hypertrophic pachymeningitis (HP), presenting as a progressive thickening of the dura mater. HP lacks an animal model to determine its underlying mechanisms. We developed a suitable animal model for the treatment of HP. Methods: We longitudinally evaluated dura in mice with a mutation (Y136F) in the linker for activation of T cells (LAT), which induced type 2 T helper (Th2) cell proliferation and IgG1 (IgG4 human equivalent) overexpression. Mice were therapeutically administered daily oral irbesartan from 3 to 6 weeks of age. Human IgG4‐related, anti‐neutrophil cytoplasmic antibody‐related, and idiopathic HP dura were also immunohistochemically examined. Results: LATY136F mice showing dural gadolinium enhancement on magnetic resonance imaging had massive infiltration of B220 + B cells, IgG1 + cells, CD138 + plasma cells, CD3 + T cells, F4/80 + macrophages, and polymorphonuclear leukocytes in the dura at 3 weeks of age, followed by marked fibrotic thickening. In dural lesions, transforming growth factor (TGF)‐ β 1 was produced preferentially in B cells and macrophages while TGF‐β receptor I (TGF‐ β RI) was markedly upregulated on fibroblasts. Quantitative western blotting revealed significant upregulation of TGF‐ β 1, TGF‐ β RI, and phosphorylated SMAD2/SMAD3 in dura of LATY136F mice aged 13 weeks. A similar upregulation of TGF‐ β RI, SMAD2/SMAD3, and phosphorylated SMAD2/SMAD3 was present in autopsied dura of all three types of human HP. Irbesartan abolished dural inflammatory cell infiltration and fibrotic thickening in all treated LATY136F mice with reduced TGF‐β1 and nonphosphorylated and phosphorylated SMAD2/SMAD3. Interpretation: TGF‐ β 1/SMAD2/SMAD3 pathway is critical in HP and is a potential novel therapeutic target.